2018
DOI: 10.1016/j.neo.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Flavonoid Composition Targets Androgen Receptor Signaling and Inhibits Prostate Cancer Growth in Preclinical Models

Abstract: The high prevalence and long latency period of prostate cancer (PCa) provide a unique opportunity to control disease progression with dietary and nutraceutical approaches. We developed ProFine, a standardized composition of luteolin, quercetin, and kaempferol, and investigated its potential as a nutraceutical for PCa in preclinical models. The three ingredients of ProFine demonstrated synergistic in vitro cytotoxicity and effectively induced apoptosis in PCa cells. ProFine markedly affected the transcriptome o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 48 publications
0
21
0
1
Order By: Relevance
“…Kaempferol has been shown to induce GM-CSF release in PC-3 cells that, in turn, increase the chemotaxis of DC through activation of phospholipase C (PLC), MEK1/2, and protein kinase C (PKC) [73]. Obviously, the transcriptome of prostate cancers cells is also markedly affected by kaempferol treatment as evidenced by the down-regulation of androgen receptor genes expression [74]. In rats, orally administered kaempferol showed no significant toxicity and significantly increased survival, in addition to reducing the growth of PCa xenografts in athymic nude mice [74].…”
Section: Anticancer Properties Of Kaempferolmentioning
confidence: 99%
“…Kaempferol has been shown to induce GM-CSF release in PC-3 cells that, in turn, increase the chemotaxis of DC through activation of phospholipase C (PLC), MEK1/2, and protein kinase C (PKC) [73]. Obviously, the transcriptome of prostate cancers cells is also markedly affected by kaempferol treatment as evidenced by the down-regulation of androgen receptor genes expression [74]. In rats, orally administered kaempferol showed no significant toxicity and significantly increased survival, in addition to reducing the growth of PCa xenografts in athymic nude mice [74].…”
Section: Anticancer Properties Of Kaempferolmentioning
confidence: 99%
“…Increased mouse survival [339,[352][353][354][355]. Reduced tumor growth and metastasis [339,[352][353][354][355][356]. Caused degranulation and accumulation of mediators in leukemia cells [357,358].…”
Section: Kaempferolmentioning
confidence: 99%
“…Studies investigating the anti-cancer effects of kaempferol in vivo were also reviewed by Irman et al [328,423]. In in vivo mouse models of various cancers, including bladder, oral, prostate, lung and bone cancers, treatment with kaempferol was able to increase survival and reduce the growth and metastasis of tumours [339,[352][353][354][355]. In a rat model of leukemia, treatment with kaempferol resulted in degranulation in basophilic leukemia cells (RBL-2H3) and increased the accumulation of mediators in human leukemic mast cells (HMC-1) [357,358].…”
Section: Kaempferolmentioning
confidence: 99%
“…Likewise, sulforaphane (an isothiocyanate) was found to downregulate the TMPRSS2 expression through the release and translocation of the Nrf2 (nuclear factor (erythroid-derived 2)-like 2) (Gibbs et al, 2009;Meyer and Jaspers, 2015). Mamouni et al (2018) found that a standardized flavonoids formulation including luteolin, quercetin, and kaempferol significantly suppressed TMPRSS2 expression. In spite of the diverse biological effects attributed to the three flavonoids, this study has demonstrated that at low concentrations, they exhibited an important synergic effect.…”
Section: Natural Products Targeting the Tmprss2mentioning
confidence: 99%